2018
DOI: 10.1111/desc.12651
|View full text |Cite
|
Sign up to set email alerts
|

Infant brain responses to felt and observed touch of hands and feet: an MEG study

Abstract: There is growing interest concerning the ways in which the human body, both one's own and that of others, is represented in the developing human brain. In two experiments with 7-month-old infants, we employed advances in infant magnetoencephalography (MEG) brain imaging to address novel questions concerning body representations in early development. Experiment 1 evaluated the spatiotemporal organization of infants' brain responses to being touched. A punctate touch to infants' hands and feet produced significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 74 publications
2
50
0
Order By: Relevance
“…Keysers et al., ). Building on this, a study with 7‐month‐old infants found that neural regions activated when infants were touched on their own hands (or feet) overlapped with the neural regions activated when infants merely observed someone else's hands (or feet) being touched (Meltzoff et al., ). Infants who saw the touch of another person's hands or feet showed activation in their somatosensory cortex not simply their visual cortex.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Keysers et al., ). Building on this, a study with 7‐month‐old infants found that neural regions activated when infants were touched on their own hands (or feet) overlapped with the neural regions activated when infants merely observed someone else's hands (or feet) being touched (Meltzoff et al., ). Infants who saw the touch of another person's hands or feet showed activation in their somatosensory cortex not simply their visual cortex.…”
Section: Discussionmentioning
confidence: 97%
“…Adult MEG studies have been able to differentiate cortical responses to various parts of the mouth including the upper lip, lower lip, and tongue (Disbrow et al., ; Hari et al., ; Nakamura et al., ). Recent advances in MEG hardware and software have established the utility of MEG for brain imaging studies of human infants (Ferjan Ramírez, Ramírez, Clarke, Taulu, & Kuhl, ; Meltzoff et al., ), and such technology may be useful in future investigations of infant neural body representations including of the mouth region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also novel investigations that focus on the role that touch plays in early experiences. For example, some researchers are focusing on the role of touch on the organization and plasticity of infant body maps (Meltzoff et al, 2018;Saby, Meltzoff, & Marshall, 2015). The examination of mother and infant touch has also been conducted in at-risk populations such as mothers with depressive symptoms (e.g., Beebe et al, 2008;Feldman, Keren, Gross-Rozval, & Tyano, 2004;Herrera, Reissland, & Shepherd, 2004;Mantis, Mercuri, Stack, & Field, 2018), and touch consistently emerges as a critical variable in developmental and clinical research.…”
mentioning
confidence: 99%